MODERN APPROACHES TO STUDYING VSEVOLOD NESTAYKO'S NOVELS "THE MAGIC TALISMAN" AND "THE BULLFIGHTERS FROM VASYUKIVKA" IN 5-6 GRADES OF NUSH - Khomyn, Ivanna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Purpose. The aim of this article is to determine the place of literary analysis in the educational process using various methodical sources. Based on the research objective, the following tasks were set: justify the theoretical principles of analyzing prose works, characterize the methodology of analyzing novels in 5-6 grades, and examine it from a synchronous perspective. Research methodology. The article applies the principles of unity of theory and practice, systematicity, and objectivity. Results showed that innovative approaches developed for Vsevolod Nestayko's novels "The Magis Talisman" and "Toreadors from Vasyukivka" effectively help students in the 5-6 grades of the New Ukrainian School (NUSh) understand the artistic content and main ideas of the works. Scientific novelty lies in revealing the possibilities for using interactive teaching methods, creative tasks, group work, and discussions that promote active student participation and the development of their literary abilities. It combines interactive and innovative methodical approaches, which activate students' cognitive activity, stimulate their interest in reading, foster critical thinking, and engage them in a deep understanding and analysis of literary works. Practical importance lies in creating a special methodical strategy that will provide Ukrainian literature teachers with optimal approaches to studying Nestayko's works in 5-6 grades. The use of innovative methodical techniques will help diversify the process of studying the works and develop students' literary competence.